Community Empowerment Program in Indonesia - Farida, Umi; Qabandiya, Muh Kholidinna (Journal of Indonesian Scholars for Social Research, 2022)
Development is an effort to increase the dignity of those people who, in their condition, are unable to escape from the trap of poverty and underdevelopment. In the context of efforts to manifest the success of development in the Mamuju Regency, it is necessary to choose paradigms and strategies used as the basis for the development process. "Community welfare" is the ideal of all nations on earth; a condition where every citizen feels comfortable, peaceful, and happy and can fulfill their needs for clothing and housing. At its most basic level, a civilized person's welfare is their ability to meet their basic needs, such as getting enough food, clothing, a place to live, good health care, and an education. Human behavior is often less conducive to efforts to realize their welfare, both individually, in family, and the community, thus causing gaps in learning about their interests. In the context of society, "empowerment" means that people can work together for the good of the whole community. When most of the people in an organization are physically and mentally healthy, educated, strong, and creative, that organization has a high level of empowerment. But in addition to the physical values mentioned above, other values in society are also sources of empowerment. These include family values, cooperation, struggle, and diversity, which are unique to our community.